Abatement and allocation in the pilot phase of the EU ETS - Barry Anderson; Corrado Di Maria; Frank Convery (Fondazione Eni Enrico Mattei (FEEM), 2009)
We use historical industrial emissions data to assess the level of abatement and overallocation that took place across European countries during the pilot phase (2005-2007)of the European Union Emission Trading Scheme. Using a dynamic panel data model, we estimate the counterfactual (business-as-usual) emissions scenario for EU member states. Comparing this baseline to allocated and verified emissions, we conclude that both overallocation and abatement occurred, along with under-allocation and emissions inflation. Over the three trading years of the pilot phase we find over-allocation of approximately 376 million EUAs (6%) and total abatement at the member state level of 107 Mt CO2 (1.8%). However, due to over-allocation and possible uncertainty about future allocation methodologies, we calculate that emissions inflation of approximately 119 Mt CO2 (2%) occurred, resulting in emissions over the pilot phase being approximately 12 Mt CO2 (0.2%) higher than they would have been in the absence of the EU ETS.
Keywords: C23; O13; Q54; Q58; 330; Emissions Trading Scheme; Climate Policy; Dynamic Panel Data Analysis